Meningkatkan Hasil Belajar PKN Dengan Penerapan Model Aptitude Treatment Interaction (Ati) Pada Siswa Kelas V Sdn 58 Kota Ternate - Iswan E. Tawari (Jurnal Ilmiah Wahana Pendidikan, 2023)
Application of the aptitude treatment interaction (ATI) learning model to improve Pkn learning outcomes for fifth grade students at SDN 58 Ternate City. This research is a class action research (Classroom Action Research). This research was conducted at SD Negeri 58 Kota Ternate. The research subjects were fifth grade students at SD Negeri 58 Kota Ternate. The research was conducted in 2023/2024. This study aims to improve the learning outcomes of Civics Class V students at SDN 58 Ternate City. Based on the research results from the results of a descriptive analysis of student learning outcomes in cycle II showed that the highest score was 91, the lowest score was 55 and the average student score was 70.8 with a standard deviation of 6.83. The number of students who complete their studies is 65.5% and 34.5% do not complete their studies. Based on the descriptive analysis above, student learning outcomes have increased after the second cycle of action, namely from an average score of 60 to 70.8 but individual learning mastery has reached 65.5%.